Orientation of the tRNA anticodon in the ribosomal P-site: quantitative footprinting with U33-modified, anticodon stem and loop domains. - Ashraf, S S (1999)
Binding of transfer RNA (tRNA) to the ribosome involves crucial tRNA-ribosomal RNA (rRNA) interactions. To better understand these interactions, U33-substituted yeast tRNA(Phe) anticodon stem and loop domains (ASLs) were used as probes of anticodon orientation on the ribosome. Orientation of the anticodon in the ribosomal P-site was assessed with a quantitative chemical footprinting method in which protection constants (Kp) quantify protection afforded to individual 16S rRNA P-site nucleosides by tRNA or synthetic ASLs. Chemical footprints of native yeast tRNA(Phe), ASL-U33, as well as ASLs containing 3-methyluridine, cytidine, or deoxyuridine at position 33 (ASL-m3U33, ASL-C33, and ASL-dU33, respectively) were compared. Yeast tRNAPhe and the ASL-U33 protected individual 16S rRNA P-site nucleosides differentially. Ribosomal binding of yeast tRNA(Phe) enhanced protection of C1400, but the ASL-U33 and U33-substituted ASLs did not. Two residues, G926 and G1338 with KpS approximately 50-60 nM, were afforded significantly greater protection by both yeast tRNA(Phe) and the ASL-U33 than other residues, such as A532, A794, C795, and A1339 (KpS approximately 100-200 nM). In contrast, protections of G926 and G1338 were greatly and differentially reduced in quantitative footprints of U33-substituted ASLs as compared with that of the ASL-U33. ASL-m3U33 and ASL-C33 protected G530, A532, A794, C795, and A1339 as well as the ASL-U33. However, protection of G926 and G1338 (KpS between 70 and 340 nM) was significantly reduced in comparison to that of the ASL-U33 (43 and 61 nM, respectively). Though protections of all P-site nucleosides by ASL-dU33 were reduced as compared to that of the ASL-U33, a proportionally greater reduction of G926 and G1338 protections was observed (KpS = 242 and 347 nM, respectively). Thus, G926 and G1338 are important to efficient P-site binding of tRNA. More importantly, when tRNA is bound in the ribosomal P-site, G926 and G1338 of 16S rRNA and the invariant U33 of tRNA are positioned close to each other.